Synthesis of Poly(lactic acid)-block-poly(N,N-dimethylaminoethyl methacrylate) Copolymers with Controllable Block Structures via Reversible Addition Fragmentation Polymerization from Aminolyzed Poly(lactic acid) - Wenwen Yu; Lijing Zhu; Jiangao Shi; Cunting Zhao (International Journal of Polymer Science)
Poly(lactic acid)-block-poly(N,N-dimethylaminoethyl methacrylate) (PLA-PDMAEMA) copolymers were synthesized from aminolyzed PLA via reversible addition fragmentation (RAFT) polymerization. PLA undergoes aminolytic degradation with ethylenediamine (EDA). The kinetics of the aminolysis reaction of PLA at different temperatures and EDA concentrations was investigated in detail. The molar masses of products rapidly decreased in the initial stage at low aminolytic degree. Meanwhile, reactive –NH2 and –OH groups were introduced to the end of shorter PLA chains and used as sites to further immobilize the RAFT agent. PLA-PDMAEMA block copolymers were synthesized. A pseudo-first-order reaction kinetics was observed for the RAFT polymerization of PDMAEMA at a low conversion. By controlling the aminolysis reaction of PLA and RAFT polymerization degree of DMAEMA, the length distributions of the PLA and PDMAEMA blocks can be controlled. This method can be extended to more systems to obtain block copolymers with controllable block structure.